2015
DOI: 10.1093/ofid/ofv122
|View full text |Cite
|
Sign up to set email alerts
|

A Survey Study of Pregnant Women and Healthcare Practitioners Assessing the Knowledge of Attitudes and Practices of Hepatitis B Management at a Teaching Hospital in Kumasi, Ghana, West Africa

Abstract: Hepatitis B virus (HBV) infection is a major global health problem, with sub-Saharan Africa (SSA), including West Africa, bearing a large proportion of cases. Mother-to-child and early childhood horizontal transmission, the most common mechanisms of disease spread in West Africa, lead to a high rate of chronic infection. Although these transmission mechanisms are preventable through vaccine and hepatitis B immunoglobulin, they are not routinely used due to limited resources. Antiviral therapy in pregnant women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 9 publications
5
8
0
Order By: Relevance
“…For instance, Mutocheluh and Kwarteng [ 62 ], reported that among 200 barbers in Kumasi none (0 %) of the barbers could describe the common HCV transmission pathways and only 7 % were aware that sharing razor blade or hair trimmer could be a means of transmitting viral pathogens like HCV and HBV. Similar trends of low awareness has been reported for pregnant women [ 63 ]. Additionally, while the transmission dynamics of HCV remains varied and include unprotected sex, mother-to-child transmission and transfusion of infected blood, in many Ghanaian communities, there has been an over-emphasis on HCV and related viral hepatitis as sexually transmitted infections (STIs) [ 13 ].…”
Section: Discussionsupporting
confidence: 85%
“…For instance, Mutocheluh and Kwarteng [ 62 ], reported that among 200 barbers in Kumasi none (0 %) of the barbers could describe the common HCV transmission pathways and only 7 % were aware that sharing razor blade or hair trimmer could be a means of transmitting viral pathogens like HCV and HBV. Similar trends of low awareness has been reported for pregnant women [ 63 ]. Additionally, while the transmission dynamics of HCV remains varied and include unprotected sex, mother-to-child transmission and transfusion of infected blood, in many Ghanaian communities, there has been an over-emphasis on HCV and related viral hepatitis as sexually transmitted infections (STIs) [ 13 ].…”
Section: Discussionsupporting
confidence: 85%
“…The high rate of willingness to take HBV vaccination discovered in the study was in line with the finding from a Ghana study showing that 93.8% of pregnant women surveyed would take medication to prevent HBV [17]. In contrast, a Chinese study stated that only 16.5% of participants would accept HBV preventive drugs during pregnancy [18].…”
Section: Discussionsupporting
confidence: 78%
“…Fourteen included studies assessed the awareness of 9,446 Africans in regard to HBV, three studies were conducted in each of Nigeria [61,62,64] , Cameroon [20,40,58] and Ghana [12,15,28] , two in Ethiopia [32,52] , one in each of Kenya, Mozambique and Madagascar [26,57,71] . The oldest among the study included was conducted in 2010 while the newest was conducted in 2016 (Table 1).…”
Section: Resultsmentioning
confidence: 99%